2012
DOI: 10.5897/jmpr11.1395
|View full text |Cite
|
Sign up to set email alerts
|

A survey of medicinal plants in mangrove and beach forests from sating Phra Peninsula, Songkhla Province, Thailand

Abstract: This study aimed to survey medicinal plants in mangrove and beach forests from Sating Phra Peninsula, Songkhla Province. Three representative districts including Sing Ha Nakhon, Sating Phra and Ranode were selected. Semi-structured interview was conducted to six local healers for asking about local names, parts of use, preparation and properties. Plant specimens also were collected. Identification was done and the specimens were deposited at The Prince of Songkla University herbarium (PSU). A total of 110 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
1
17
1
Order By: Relevance
“…According to habitat, plants from sandy forests were found more species than swamp (71 and 28 species respectively). This result is consistent to the study from nearby area, Sating Phra peninsula, Thailand (Neamsuvan et al, 2012) which revealed more plant species from beach forests than wetland areas.…”
Section: Diversity Of Medicinal Plantssupporting
confidence: 81%
See 2 more Smart Citations
“…According to habitat, plants from sandy forests were found more species than swamp (71 and 28 species respectively). This result is consistent to the study from nearby area, Sating Phra peninsula, Thailand (Neamsuvan et al, 2012) which revealed more plant species from beach forests than wetland areas.…”
Section: Diversity Of Medicinal Plantssupporting
confidence: 81%
“…Comparison to related studies This study was compared to a survey of adjacent areas in mangrove and beach forests from Sating Phra Peninsula, Songkhla province, Thailand (Neamsuvan et al, 2012). It was found that 13 medicinal species are similar used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They produce small sized fruits pinkish in colour. Their leaves are traditionally used as cardiotonic, antenatal care and rhizome are used as a treatment for fever, malaria and jaundice [24].…”
Section: Resultsmentioning
confidence: 99%
“…Thetree has multiple uses of all its parts. Leaves are used to treat fever, inflammation, ulcer, induce lactation and rheumatic pains, meanwhile root or stem are used to relieve joint and muscle pain [24], [41], [42].…”
Section: Resultsmentioning
confidence: 99%